Innovative Strategies in Improving the Quality of Learning in Digital-Based Elementary Schools - Wildan Zaenur Romdhoni; Choirul Anam; Syahrudin Syahrudin (LP3M Pascasarjana STAI Ibnurusyd, 2025)
This study aims to explore innovative strategies in improving the quality of learning in digital-based schools. With a qualitative approach, this study explores the experiences, challenges, and solutions implemented by educators in utilizing digital technology optimally. Data collection was carried out through in-depth interviews, participant observation, and documentation studies in several schools that have implemented digital learning models. The results of the study indicate that effective innovative strategies include the use of interactive learning platforms, dynamic virtual classroom management, and the integration of educational applications that support collaborative learning. In addition, support for technology training for teachers and the development of a digital literacy culture among students have proven to be key factors in creating a meaningful and adaptive learning process. These findings confirm that the creative use of technology not only improves learning outcomes but also builds 21st-century skills such as critical thinking, communication, and collaboration. Thus, this study is expected to be a reference for policy makers and education practitioners in designing innovative, effective, and student-oriented learning strategies in the digital era.